Classification of Dates Based on Texture Using Local Binary Pattern Algorithm and Support Vector Machine - Mhd Furqan; Sriani Sriani; Suci Syahputri (Jurnal Nasional Komputasi dan Teknologi Informasi (JNKTI), 2025)
Abstract - Dates are a food that is widely favored by Muslims in Indonesia, especially during the month of Ramadan. The many types of dates make it difficult to distinguish the types of dates. To distinguish the types of dates can be seen from the shape, color, size or texture. In this study, dates will be distinguished based on their texture. Local Binary Pattern is one of the algorithms that can be used to extract images of dates based on their texture by comparing the center value of the pixel with the value of the surrounding pixels to facilitate the classification process. The classification used uses Support Vector Machine which works by finding the best hyperplane to determine data for each class. The combination of these two algorithms has proven to be able to classify with an accuracy level of 93%.Keywords: Classification, Local Binary Pattern, Support Vector Machine, Dates Abstrak - Kurma adalah makanan yang sangat disukai oleh umat Muslim di Indonesia, terutama selama bulan Ramadan. Beragam jenis kurma membuatnya sulit untuk membedakan jenis-jenis kurma tersebut. Untuk membedakan jenis kurma dapat dilihat dari bentuk, warna, ukuran, atau teksturnya. Dalam penelitian ini, kurma akan dibedakan berdasarkan teksturnya. Local Binary Pattern (LBP) adalah salah satu algoritma yang dapat digunakan untuk mengekstrak gambar kurma berdasarkan teksturnya dengan membandingkan nilai pusat piksel dengan nilai piksel di sekitarnya untuk memudahkan proses klasifikasi. Klasifikasi yang digunakan menggunakan Support Vector Machine (SVM) yang bekerja dengan mencari hiperplane terbaik untuk menentukan data untuk setiap kelas. Kombinasi kedua algoritma ini terbukti mampu mengklasifikasikan dengan tingkat akurasi 93%.Kata kunci: Klasifikasi, Local Binary Pattern, Support Vector Machine, Kurma